2016
DOI: 10.1097/sap.0000000000000519
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intraoperative Fluorescent Indocyanine Green Angiography for Real-Time Vascular Evaluation of Pericranial Flaps

Abstract: Anteriorly based PCF had significantly better vascularity compared to laterally based PCF and seemed safer to harvest regardless of flap pedicle type. Also, the feasibility of harvesting muscle sparing laterally based PCF was indicated. Finally, being older than 45 years, a body mass index more than 25, or being a smoker might increase the risk of reducing flap vascularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Forty-nine articles, including 1996 surgical flaps, were selected for the review. Study designs included prospective cohort studies (n = 27), 31,34,35,38,39,[41][42][43][47][48][49][50]56,[58][59][60][62][63][64][65][66][67][68][69][70][71] retrospective cohort studies (n = 16), [25][26][27]29,32,33,36,40,44,45,51,55,57,61,72 prospective pilot studies (n = 3), 28,37,52 and retrospective case series (n = 3). 46,53,54 No randomized controlled trials have been performed yet that concern ICGA in plastic and reconstructive flap surgery.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-nine articles, including 1996 surgical flaps, were selected for the review. Study designs included prospective cohort studies (n = 27), 31,34,35,38,39,[41][42][43][47][48][49][50]56,[58][59][60][62][63][64][65][66][67][68][69][70][71] retrospective cohort studies (n = 16), [25][26][27]29,32,33,36,40,44,45,51,55,57,61,72 prospective pilot studies (n = 3), 28,37,52 and retrospective case series (n = 3). 46,53,54 No randomized controlled trials have been performed yet that concern ICGA in plastic and reconstructive flap surgery.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Indocyanine green angiography has been reported for several types of flaps in plastic and reconstructive flap surgery in a clinical setting. The majority of included articles used ICGA to assess tissue perfusion of mastectomy skin flap (n = 14) intraoperatively 25,26,[31][32][33][39][40][41]47,51,55,57,58,61 ; the remainder focused on the intraoperative assessment of nipple-areolar complex perfusion, 27,72 a combination of nipple-areolar complex and mastectomy skin flap perfusion, 24 anterolateral thigh flap, 28,29 deep inferior epigastric perforator flap, 38,56,66 transverse rectus abdominis myocutaneous flap, 38,56,70 superficial inferior epigastric artery flap, 64,65,73 superficial circrumflex iliac artery flap, 50 free pericranial flap, 36 latissimus dorsi flap, 34 free parascapular flaps, 63 paramedian forehead flap, 43 intercostal muscle flap, 52 osseus free flaps, 44 free fibula flap, 45 and various pedicled and/or free flaps. 30,35,37,42,46,48,53,54,59,…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, vascularization of anteriorly based PCF was found to be superior to laterally based flaps in a recent experimental study, suggesting a more reliable and durable reconstruction. 11 An extracranial PCF minimizes the morbidity of PCF reconstruction by avoiding a craniotomy. There is also potential for minimally invasive endoscopic harvest.…”
Section: Discussionmentioning
confidence: 99%
“…ICGA is widely used due to its technical simplicity and low risk of complications. 6 In the field of plastic surgery, ICGA is used in various procedures including the evaluation of elevated flaps, 7–10 identification of perforator vessels, 11–13 and assessment of blood perfusion to nerves. 14 Previous studies reported that rates of postoperative flap necrosis were improved by intraoperative ICGA-guided trimming.…”
Section: Introductionmentioning
confidence: 99%